Mechanical-force-induced non-local collective ferroelastic switching in epitaxial lead-titanate thin films - Xiaoyan Lu (Nature Portfolio, 2019)
Clamping effects in ferroelestastic thin films limits their usefulness for applications such as sensitive mechanical sensors. Here, the authors report on non-local mechanical force induced switching in PbTiO3 thin films by tuning the material to a state of nearly energetically degenerate co-existing domains.